2021
DOI: 10.1097/wco.0000000000001005
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular disease in pregnancy and postpartum

Abstract: Purpose of reviewCerebrovascular disorders during pregnancy and puerperium are uncommon but potentially serious entities. This review aims to provide guidance on the diagnosis and management of these diseases, according to the most recent findings. Recent findingsProteinuria is no longer a mandatory criterion for the diagnosis of preeclampsia. Favourable long-term foetal and maternal outcomes are achieved in most patients with ruptured cerebral arterial malformations during pregnancy receiving interventional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 77 publications
0
10
0
1
Order By: Relevance
“…9,30 Additional studies are needed to further evaluate the mechanisms underlying our observed associations. Although associations between pregnancy, the postpartum period, and stroke have been previously explored, [31][32][33] relationships between ART and stroke have received less attention. A recent retrospective cohort study by Sachdev et al 10 using data from the Nationwide Readmissions Database in the United States found that ART was associated with an increased risk of stroke-related hospitalization within 1 year of delivery and that this risk was evident as early as 1 month after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…9,30 Additional studies are needed to further evaluate the mechanisms underlying our observed associations. Although associations between pregnancy, the postpartum period, and stroke have been previously explored, [31][32][33] relationships between ART and stroke have received less attention. A recent retrospective cohort study by Sachdev et al 10 using data from the Nationwide Readmissions Database in the United States found that ART was associated with an increased risk of stroke-related hospitalization within 1 year of delivery and that this risk was evident as early as 1 month after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The era of one person holding multiple jobs and cross bank robbery has become a trend of social development, which has led to a fast pace of life, increased pressure, a general increase in the incidence of various diseases, and the problem of food and clothing for people has been solved. The variety of diet is becoming more and more abundant, the diet structure of life has changed dramatically, the incidence rate of cerebrovascular disease has increased year by year, its disease progress is fast and the disability rate is high, so it has become the "first key" to threaten people's health [2] . In the latest national survey on the causes of death of residents, the health department found that the total death toll of acute cerebrovascular disease was about (136/100 000), which has far exceeded lung cancer, esophageal cancer, breast cancer and other malignant tumor diseases and ranked first in the overall cause of death in China.…”
Section: Current Research Status Of Acute Cerebrovascular Diseasementioning
confidence: 99%
“…Cerebrovascular disease is characterized by high incidence rate, high recurrence rate, high disability rate and high mortality [1] . With the aging population and significant improvement of living standards in China, the incidence of cerebrovascular diseases has increased at an average annual rate of 8.3 %, ranking first among the causes of death among Chinese residents and being the main cause of illness and death in patients with the nervous system [2] . The incidence of acute severe cerebrovascular disease is also increasing year by year with the increasing incidence of cerebrovascular diseases, which is the focus of attention in the medical community.…”
mentioning
confidence: 99%
“…Eine seltene, jedoch schwerwiegende Komplikation der Präeklampsie ist das posteriore reversible Enzephalopathie-Syndrom (PRES). Es stellt aufgrund des klinischen Erscheinungsbildes eine komplexe Differentialdiagnose dar 10 11 . Im Verlauf der Pandemie wurde das PRES auch im Rahmen akuter SARS-CoV-2-Infektionen bei nicht-schwangeren und schwangeren Patientinnen beschrieben 12 13 14 .…”
Section: Introductionunclassified